2014
DOI: 10.1002/tox.22013
|View full text |Cite
|
Sign up to set email alerts
|

Oral exposure of pubertal male mice to endocrine-disrupting chemicals alters fat metabolism in adult livers

Abstract: The potential for the exposure of humans and wildlife to environmental endocrine-disrupting chemicals (EDCs) has been increasing. Risk assessment for such EDCs is primarily based on detecting the main endpoints related to the endocrine and reproductive systems, while the effects on glucose and fat metabolism have only received limited attention. In this study, pubertal male C57BL/6J mice were orally administered 10 mg/kg body weight cypermethrin (CYP), 100 mg/kg body weight atrazine (ATZ), and 0.1 mg/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
(53 reference statements)
2
19
1
Order By: Relevance
“…These results agree with those of Rogers et al , who observed increased relative liver, kidney, and spleen weights in rats exposed to naphthenic acids from oil sands tailings. Increased masses of these organs in animals exposed to endocrine disruptors have been attributed to edema or histopathological alterations possibly mediated by metabolic dysregulation . However, the relatively low doses of contaminants used in the present study suggest that the changes in scaled liver index and scaled kidney index are from physiological responses to pollutant exposure such as the activation of detoxifying metabolic routes , rather than from pathological changes, even though we did not detect increased ethoxyresorufin O ‐deethylase induction.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These results agree with those of Rogers et al , who observed increased relative liver, kidney, and spleen weights in rats exposed to naphthenic acids from oil sands tailings. Increased masses of these organs in animals exposed to endocrine disruptors have been attributed to edema or histopathological alterations possibly mediated by metabolic dysregulation . However, the relatively low doses of contaminants used in the present study suggest that the changes in scaled liver index and scaled kidney index are from physiological responses to pollutant exposure such as the activation of detoxifying metabolic routes , rather than from pathological changes, even though we did not detect increased ethoxyresorufin O ‐deethylase induction.…”
Section: Discussioncontrasting
confidence: 74%
“…We consider that differences among groups for body condition at the end of the experiment, especially the increased body condition of the metals þ alkyl-PAHs group compared with controls, are confounded by the fact that mice exposed to alkyl-PAHs and metals þ alkyl-PAHs had relatively heavier livers, spleens, and kidneys, thus resulting in an apparent, but not truly better, body condition. However, exposure to low dosages of endocrine-disrupting chemicals can cause slight increases in body weight through disruption of normal homeostatic controls of adipogenesis and energy balance, whereas weight loss occurs after higher doses of exposure along with other signs of systemic toxicity [60,61]. The present study's hypothesis is partially supported by the results of Tête et al [62] in wild mice captured along a metal pollution gradient, who found that scaled mass index increased with Cd concentrations in both liver and kidneys of animals living in lightly and moderately polluted areas, whereas the relationship became inverted for animals trapped in highly polluted sites.…”
Section: Body Condition and Organosomatic Indicesmentioning
confidence: 99%
“…These reagent kits have been validated in published papers for fish (Du et al, 2015;Jia, Cao, Xu, Jeney, & Yin, 2012;Jin et al, 2015). These reagent kits have been validated in published papers for fish (Du et al, 2015;Jia, Cao, Xu, Jeney, & Yin, 2012;Jin et al, 2015).…”
Section: Analysis Of Haematological Parametersmentioning
confidence: 99%
“…Recent study showed that ATZ also affects DNA methylation in plants (38). In mammals, ATZ exposure affects many tissues, including testes (3942), ovaries (4347), brain (48,49), liver (5054) and the presence of low dose metabolites of ATZ is associated with low birth weight in human (55). …”
Section: Introductionmentioning
confidence: 99%